IMPLEMENTASI KEBIJAKAN TATA CARA PEMBUKAAN LAHAN BAGI MASYARAKAT DALAM PENANGANAN KEBAKARAN HUTAN DAN LAHAN (KARHUTLA) DI KABUPATEN SINTANG PROVINSI KALIMANTAN BARAT - Selvia Junita Praja; Margaretha Rumbekwan; Rio Noperando (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2020)
Forest and Land Fires in Sintang Regency Always occur every year with unstable conditions, where Forestand Land Fires have a very detrimental impact on the Community and the Government of Sintang, so that the Government of Sintang District issued Sintang District Regulations Number 57 of 2018 concerning LandClearing Procedures for the Community. In this regard, researchers are interested in conducting researchunder the title "Implementation of Land-Opening Policy Procedures for Communities in Handling Forest and Land Fires (karhutla) in Sintang District, West Kalimantan Province". This study aims to find out how theimplementation of the policy for Land Clearing Procedures of karhutla in Sintang District. The research usesqualitative method with descriptive approach. Researchers used data collection techniques such asinterviews, observation, and documentation. Based on the results of research conducted using the Van Meter and Van Horn Policy Implementation model, it can be found that the implementation of the policy on land clearing procedures of karhutla in Sintang district is still not optimal. This can be seen from the cases offorest and land fires in Sintang District that continue to occur, even with the same conditions as in previousyears, many people as policy targets do not understand and do not know the policy, and still lack adequateunderstanding of policy implementers of the policies. Keywords: Implementation of Policies, Forest and Land Fires, Procedures for Land Clearing, Sintang